Silver–Bismuth Halide Double Salts for Lead‐Free Photovoltaics: Insights from Symmetry‐Based Modeling. Issue 12 (11th December 2022) - Cucco, Bruno; Pedesseau, Laurent; Katan, Claudine; Even, Jacky; Kepenekian, Mikaël; Volonakis, George
Abstract : Lead‐Free Photovoltaics In article number 2200718, Mikaël Kepenekian, George Volonakis, and co‐workers explore silver‐bismuth halide double salts, also called rudorffites, employing a symmetry‐based modelling approach. The developed method successfully describes the structural, electronic, and optical properties of materials AgBiI4 and Ag3 BiI6 . Their ideal photovoltaic performance is established and compared with the one of silver‐bismuth halide double perovskites, highlighting their potential as absorbers for solar cells.